The Influence of Communication And Work Conflict on Employee Performance At The Secretariat of DPRD North Sumatra - Ayu Intan Pratiwi; Nuri Aslami; Rahmat Daim Harahap (Quantitative Economics and Management Studies, 2023)
The smooth operation and success of the company's vision, mission and goals depend heavily on continuous and well-established communication within the organization. This includes communication from superior to subordinate, from subordinate to superior and communication between colleagues. However, due to the ability of subordinates, communication becomes an inhibiting factor in the delivery of messages conveyed or sent by subordinates to superiors. The purpose of this study was to determine and analyze the effect of communication and work conflict on employee performance at the North Sumatra DPRD Secretariat. This research is a type of association research. This research was conducted at the DPRD Secretariat of North Sumatra. The method used in this research is descriptive statistical method with a quantitative approach, the sampling technique used in this research is a questionnaire. Based on the information the author received from the Administrative Section of the North Sumatra DPRD Secretariat, the number of employees in the property reaches 50 employees. Data collection techniques using data instrument tests, knowledge needs tests, and statistical tests. The results of this study indicate that communication and work conflict simultaneously affect the performance of employees at the DPRD Secretariat of North Sumatra. Partially, communication and work conflict have a significant and positive effect on employee performance at the North Sumatra DPRD Secretariat.